2015
DOI: 10.1007/7651_2015_230
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation of Pluripotent Stem Cells into Functional β Islets Under 2D and 3D Culture Conditions and In Vivo Preclinical Validation of 3D Islets

Abstract: Since the advent of pluripotent stem cells, (embryonic and induced pluripotent stem cells), applications of such pluripotent stem cells are of prime importance. Indeed, scientists are involved in studying the basic biology of pluripotent stem cells, but equal impetus is there to direct the pluripotent stem cells into multiple lineages for cell therapy applications. Scientists across the globe have been successful, to a certain extent, in obtaining cells of definitive endoderm and also pancreatic β islets by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
2
5
0
Order By: Relevance
“…CMs generated from human induced pluripotent stem cells (hiPSCs) may offer a platform to study disease mechanism and evaluate novel drugs. However, hiPSC-CMs are believed to consist predominantly of ventricular-like cells with a small percentage of atrial-like and nodal-like cells (van den Berg et al., 2016, Blazeski et al., 2012, Ma et al., 2011, Marczenke et al., 2017). Recent developments therefore aim at establishing hiPSC-derived models of predominantly atrial-like myocytes.…”
Section: Introductionmentioning
confidence: 99%
“…CMs generated from human induced pluripotent stem cells (hiPSCs) may offer a platform to study disease mechanism and evaluate novel drugs. However, hiPSC-CMs are believed to consist predominantly of ventricular-like cells with a small percentage of atrial-like and nodal-like cells (van den Berg et al., 2016, Blazeski et al., 2012, Ma et al., 2011, Marczenke et al., 2017). Recent developments therefore aim at establishing hiPSC-derived models of predominantly atrial-like myocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicates that Pdx1 can activate downstream target genes to induce differentiation into pancreatic cells. In recent years, ESCs have been induced to differentiate into insulin-secreting cells and islet-like cells [33,34] in vitro. Our results revealed that pancreatic precursor cells (Pdx1 + cells) can differentiate into several types of pancreatic-like cells: exocrine cells and ductal cells during the early stage and endocrine cells at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…If appropriate facilities, equipment, sterile reagents and aseptic techniques are used, there is no need to use antibiotics during cell structure (single layer /2D vs. suspension/3D), pathway modulator and a transcriptional memory of the cells may also affect differentiation [9][10][11].…”
Section: Use Of Antibioticsmentioning
confidence: 99%